Comparison of Four Methods of RNA Extraction and cDNA Synthesis from The Venom of Peruvian Snakes of the Genus Bothrops of Clinical Importance - Torrejón, D.; Cardenas, J.; Juarez, D.; Espinoza, J.; Proleón, A.; Agurto-Arteaga, A.; Lazo, F.; Leguia, M.; Urra, F.A.; S?nchez, E.F.; Chavéz-Olórtegui, C.; Vivas-Ruiz, D.E.; et al. (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
RNA purification and cDNA synthesis represents the starting point for molecular analyses of snake venom proteins-enzymes. Usually, the sacrifice of snakes is necessary for venom gland extraction to identify protein-coding transcripts; however, the venom can be used as a source of transcripts. Although there are methods for obtaining RNA from venom, no comparative analysis has been conducted in the Bothrops genus. In the present study, we compared four commercial methods for RNA purification and cDNA synthesis from venom (liquid, lyophilized, or long-term storage) of four clinically relevant species of Peruvian Bothrops. Our results show that the TRIzol method presents the highest yield of RNA purified from venom (59 ± 11 ng/100 µL or 10 mg). The SuperScript First-Strand Synthesis System kit produced high amounts of cDNA (3.2 ± 1.2 ng cDNA/ng RNA), and the highest value was from combination with the Dynabeads mRNA DIRECT kit (4.8 ± 2.0 ng cDNA/ng RNA). The utility of cDNA was demonstrated with the amplification of six relevant toxins: thrombin-like enzymes, P-I and P-III metalloproteinases, acid and basic phospholipases A2, and disintegrins. To our knowledge, this is the first comparative study of RNA purification and cDNA synthesis methodologies from Bothrops genus venom.
Keywords: Complementary DNA; Venom; RNA; Trizol; Biology; Snake venom; Molecular biology; RNA extraction; Messenger RNA; Biochemistry; Bothrops; Rapid amplification of cDNA ends; cDNA library; Gene; Molecular cloning; https://purl.org/pe-repo/ocde/ford#1.06.03